ON THE HORIZON I SEE WATER: AN ANALYSIS OF THREE WATERS, A PROJECT OF PUBLIC ART IN/FOR TOLEDO (Palíndromo, 2019)
We  propose  an  analysis  of  the  Tres Aguas  project,  starting  from  the  presen-tation of a series of events. The reflection addresses three aspects: the relationship between  past  and  present,  the  city  as  a  place  of  distribution  of  the  sensible  and  art  in  public  space.  To  support  our  ap-proach, we rely on Jacques Rancière.
Keywords: Urban intervention; Distribution of the sensible; Toledo; Cristina Iglesias